Strength Training Reduces Fat Accumulation and Improves Blood Lipid Profile Even in the Absence of Skeletal Muscle Hypertrophy in High-Fat Diet-Induced Obese Condition - Catarina Denise Entringer Contreiro; Leonardo Carvalho Caldas; Breno Valentim Nogueira; André Soares Leopoldo; Ana Paula Lima-Leopoldo; Lucas Guimarães‐Ferreira (Hindawi Limited, 2020)
The aim was to investigate the effect of strength training on skeletal muscle morphology and metabolic adaptations in obese rats fed with unsaturated high-fat diet (HFD). The hypothesis was that strength training induces positive metabolic adaptations in obese rats despite impaired muscle hypertrophy. Male Wistar rats (n = 58) were randomized into two groups and fed a standard diet or a high-fat diet (HFD) containing 49.2% of fat. After induction and maintenance to obesity, the rats were divided into four groups: animals distributed in sedentary control (CS), control submitted to strength training protocol (CT), obese sedentary (ObS), and obese submitted to strength training protocol (ObT). The exercise protocol consisted of 10 weeks of training on a vertical ladder (three times a week) with a load attached to the animal's tail. At the end of 10 weeks, strength training promoted positive changes in the body composition and metabolic parameters in obese animals. Specifically, ObT animals presented a reduction of 22.6% and 14.3% in body fat and adiposity index when compared to ObS, respectively. Furthermore, these rats had lower levels of triglycerides (ObT = 23.1 ± 9.5 vs. ObS = 30.4 ± 6.9 mg/dL) and leptin (ObT = 13.2 ± 7.2 vs. ObS = 20.5 ± 4.3 ng/mL). Training (ObT and CT) induced a greater strength gain when compared with the respective control groups. In addition, the weight of the flexor hallucis longus (FHL) muscle was higher in the ObT group than in the CT group, representing an increase of 26.1%. However, training did not promote hypertrophy as observed by a similar cross-sectional area of the FHL and plantar muscles. Based on these results, high-intensity strength training promoted an improvement of body composition and metabolic profile in obese rats that were fed a high-fat diet without skeletal muscle adaptations, becoming a relevant complementary strategy for the treatment of obesity.